Biochemical variations of serum magnesium and lipid analytes in diabetes mellitus: a cross-sectional study - Fariha Muzammil; Huda Abbas; Shazia Naz; Hamza Muzammil; Wajahat Hussain (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Hypomagnesemia has a detrimental influence on glucose homeostasis and insulin sensitivity in T1DM andT2DM patients, as seen by the progression of DM comorbidities such as arterial atherosclerotic(atherosclerosis), retinopathy, and nephropathy. The objective of this study is to make a comparison and correspond biochemical variants(to analyze the difference) of fasting blood glucose, serum magnesium, and major lipid analytes (serum total cholesterol and triacylglycerol) in diverse medical groups of both T1DM and T2DM. METHODOLOGY: It was a cross-sectional observational study carried out at Sahiwal teaching hospital, Sahiwal, Pakistan, including 250 research participants. The study used a traditional time-bound sample size of 6 months starting from first March to August 2021through a random selection approach. RESULTS: Out of 250 participants, 200(80%) of whom(omit) had diabetes mellitus (DM), The number of men with diabetes 110(55%) was greater than the percentage of women with diabetes 90(45%) in this study. 52(26%) of the research participants had T1DM, whereas 148 (74%) had T2DM. A comparison of plasma glucose levels of the three groups was made, and the difference(added) was statistically significant. The difference(added) in serum magnesium, serum total cholesterol, and serum triglycerol among the groups(added) was also statistically significant p<0.05. CONCLUSION: The current study looked at hypomagnesemia biochemical changes in overt hyperglycemic-hyperlipidemic clinical groups of T1DM and T2DM. In light of the reviewed research findings, it is recommended that serum magnesium can be measured as a routine or extended diagnostic profile investigation in recognized health cases of T1DM and T2DM for early screening, periodic monitoring for deficiency, and better management of clinical cases through supplementation to prevent the development of long-term critical diabetes complications.